Implementation of Automatic Blocking System in the Management of Non-Tax State Revenue Receivables - Subardianta, Ari Untung (International Publisher, 2022)
The author's aim in conducting this research is to analyze the role of the Automatic Blocking system policy in reducing non-tax state revenue receivables. The research method used is a descriptive qualitative approach, because this research aims to obtain an overview of what is being studied to reveal problems in the performance of government organizations and observation, interviews, literature studies and documentation. Data sources were obtained from informants through direct observation and interviews and documents were obtained in the form of regulations and data processing. Based on the research, the results obtained show that the role of the ABS policy on the Automatic Blocking system policy in reducing non-tax state revenue receivables is as an effort to speed up the settlement of state receivables, provide support to the Bank Indonesia Liquidity Assistance (BLBI) task force, enrich collection efforts including by carrying out civil actions and /or termination of public services, strengthening PUPN's duties and authority. Regarding the implementation of the Government's ABS (Automatic Blocking System), in this case the Ministry of Finance has stated that the implementation of the Automatic Blocking System has been effective in encouraging Payers to settle Non-Tax State Revenue (PNBP) receivables.